Strengthening Regional Arts Competitions in Banyuwangi: Enhancing Creativity and Local Arts Development through Event Management Workshops - Arif Hidajad; Anik Juwariyah; Retnayu Prasetyanti Sekti; Eko Wahyuni Rahayu; I Nengah Mariasa (Maneggio, 2025)
Regional art competitions have strategic potential as instruments for developing local art ecosystems, yet in practice they are often reduced to ceremonial, event-oriented agendas. This condition limits their contribution to strengthening artistic creativity and the sustainability of local arts. This study aims to analyze the role of event management workshops in improving the quality of regional art competition management and its impact on artists’ creativity and sustainable local art development in Banyuwangi. The study employs a qualitative descriptive-analytical method with a contextual and interpretative approach. Data were collected through in-depth interviews with art competition organizers, local artists, and workshop facilitators, as well as document analysis of cultural policies and art programs. The findings indicate that event management workshops function as a capacity-building intervention that transforms management paradigms, strengthens strategic planning, curation systems, and stakeholder networking. Professionally managed art competitions create conducive environments for creative experimentation, reflective learning, and the sustainability of local artistic practices. This study concludes that strengthening managerial capacity through event management workshops is a key strategy for transforming regional art competitions into sustainable instruments for local art ecosystem development.